KwaThwaleyakhe Shelter: the excavation of mid and late Holocene deposits in the central Thukela Basin, Natal, South Africa - Mazel, A. D. (Southern African Humanities, 2021)
The excavation of kwaThwaleyakhe Shelter in the central Thukela Basin is reported. The site was occupied by hunter-gatherers during the mid and late Holocene. The lithic and non-lithic cultural and faunal assemblages recovered during excavations are described. Human bone remains were recovered and these are described. Despite problems associated with the provenance of some of the finds due to post-depositional disturbance, the assemblages recovered provide much new information about Thukela Basin hunter-gatherer history. The site contains cultural and subsistence items not known previously from the Natal hunter-gatherer archaeological record such as divination bones and quantities of tortoise bones. The position of kwaThwaleyakhe in terms of the 4000-2000 BP social regions, previously hypothesized, is investigated. It is concluded that this site has more in common with the sites to the north of the Thukela River than those to the south. However, there are some differences between kwaThwaleyakhe and the sites to the north and the possibility exists that this site belongs to another social region situated in the central Thukela Basin. Considering hunter-gatherer/agriculturist relations, this site provides further evidence of close contact between these communities following the arrival of the agriculturists.